Developments in virus-like particle-based vaccines for HIV. (February 2013) - Buonaguro, Luigi; Tagliamonte, Maria; Visciano, Maria Luisa; Tornesello, Maria Lina; Buonaguro, Franco M
Virus-like particles (VLPs) hold great promise for the development of effective and affordable vaccines. VLPs, indeed, are suitable for presentation and efficient delivery to antigen-presenting cells of linear as well as conformational antigens. This will ultimately result in a crosspresentation with both MHC class I and II molecules to prime CD4 + T-helper and CD8 + cytotoxic T cells. This review describes an update on the development and use of VLPs as vaccine approaches for HIV.